‘The mean mummy way’ – experiences of parents instilling eye drops to their young children as described in online forums and blogs - Law, Gloria Chun Yi (2021)
Background: Adults often have difficulty instilling eye drops in their own eyes, but little has been documented about the difficulties experienced by parents when administering eye drops to their young children, where the challenges of instillation are accentuated by their inability to cooperate. This qualitative study explores parents’ experiences of administering eye drops to their children as described in online forum discussions and blog posts. Methods: This was an exploratory study using qualitative methods. We thematically analysed the written exchanges between parents participating in online forum discussions and blog posts about the administration of eye drops to their young children. Results: We found 64 forum discussion threads and 4 blog posts, representing 464 unique contributors expressing their experiences of eye drop administration to young children. Three major themes were identified – administration challenges, administration methods and role of health care professionals. Besides describing their children’s distress, parents discussed their own discomfort and anxiety when administering eye drops. Parents used a variety of techniques to facilitate adherence with medication, including restraining the child, role-play, reassurance, distraction, or reward. The ideas exchanged about eye drop administration occasionally included reiteration of professional advice, but were dominated by parents’ own ideas/suggestions; interestingly health care professionals were considered diagnosticians and prescribers, rather than sources of practical advice on administration. Conclusions: Parents struggling to deliver eye drops to their young children may seek advice on how to administer treatment from parental on-line discussion forums. The distress experienced by the young child and their parents is a powerful reminder to clinicians that procedures common and routine in health care may be challenging to parents. The advice given to parents needs to go beyond the instillation of the eye drops, and include advice on child restraint, distraction techniques and allaying distress. Forewarned of the potential difficulties and provided with coping strategies parents can employ when the child resists, could alleviate their own and their child’s distress.